Validation of Inventory Responses-oMR (IR-oMR) towards the Self- Assesment Instrument of Outdoor Competency (OCL-oMR) among the Co-curriculum center coaches in Malaysia - Omar Firdaus Mohd Said (Tanjong Malim, 2020)
Validation of Inventory Responses-oMR (IR-oMR) towards the Self- Assesment Instrument of Outdoor Competency (OCL-oMR) among the Co-curriculum center coaches in Malaysia by Omar Firdaus Mohd Said